Recent developments in 2D layered inorganic nanomaterials for sensing - Kannan, Padmanathan Karthick; Late, Dattatray J.; Morgan, Hywel; Rout, Chandra Sekhar (Nanoscale, 2015)
Two dimensional layered inorganic nanomaterials (2D-LINs) have recently attracted huge interest because of their unique thickness dependent physical and chemical properties and potential technological applications. The properties of these layered materials can be tuned via both physical and chemical processes. Some 2D layered inorganic nanomaterials like MoS2, WS2 and SnS2 have been recently developed and employed in various applications, including new sensors because of their layer-dependent electrical properties. This article presents a comprehensive overview of recent developments in the application of 2D layered inorganic nanomaterials as sensors. Some of the salient features of 2D materials for different sensing applications are discussed, including gas sensing, electrochemical sensing, SERS and biosensing, SERS sensing and photodetection. The working principles of the sensors are also discussed together with examples.

Future prospects of 2D materials for sensing applications - Morgan, Hywel; Rout, Chandra S.; Late, Dattatray J. (Fundamentals and Sensing Applications of 2D Materials, 2019)
Two-dimensional (2D) material attracted significant research interest from the discovery of graphene in 2004. These 2D materials allow a platform for artificial integration of heterostructures with unique platforms that show exotic physical attributes and phenomenon as well as properties and applications. Each layer in 2D materials consist of a covalent bond, a dangling bond-free lattice, and weak van der Waals (vdWs) interaction. This makes it feasible to fabricate lateral and vertical vdWs heterostructures without the constraints of lattice matching and processing compatibility. These vdWs heterostructures open a door for a broad range of applications in electronics, optoelectronics, flexible devices, sensors, and photovoltaics. In this chapter, we have critically assessed the recent developments in 2D materials, the fabrication of heterostructures, and their application for sensing purposes. We conclude with current challenges and ideas concerning future developments in this merging field.

Introduction - Morgan, Hywel; Rout, Chandra S.; Late, Dattatray J. (Fundamentals and Sensing Applications of 2D Materials, 2019)
The book provides comprehensive and updated research contribution about advances in synthesis/growth of 2D materials for various sensor applications, their working principles, and mechanism behind the sensor as well physics and chemistry of materials.